Modeling and Bumpless Switching Control of Symmetrical Dual Three-Phase PMSM in Two Operating Modes. Issue 3 (7th February 2020) - Liang, Zhe; Liang, Deliang; Kou, Peng; Ze, Qiji
Abstract: This paper presents a frequency-domain model of the symmetrical dual three-phase permanent magnet synchronous machine (PMSM) in two working modes. Compared with traditional time-domain model, the presented frequency-domain model has simple expression and can be easily used in control system design and compensation. Furthermore, a frequency-model-based field oriented control (FOC) scheme for this machine is proposed. In this control scheme, parameters of proportional-integral (PI) controllers are analytically designed which can flexibly adjust the steady and dynamic performance of the entire closed-loop system. Moreover, this control strategy allows the drive system to bumpless switch between two operating modes without stopping. Finally, the developed control scheme was verified via simulations and experiments.